... someone solve this problem by complex integration, but i don't know it;
please help me to solve this problem ..!
Since you mention complex integration, try the following. The complex sine is defined as
$\displaystyle \sin w = \frac{1}{2i}(e^{iw}-e^{-iw})$
Your integrand becomes
$\displaystyle \sin(nx)\sin^m x = \frac{e^{inx}-e^{-inx}}{2i}\frac{(e^{ix}-e^{-ix})^m}{(2i)^m}$
Let $\displaystyle z = e^{ix}$. To find the integral we also need to see how $\displaystyle dx$ transforms. $\displaystyle dz = d(e^{ix}) = ie^{ix} dx = iz dx$, so $\displaystyle dx = dz/(iz)$ and so the integrand becomes
$\displaystyle 2^{-m-1}i^{-m-2}(z^n-z^{-n})(z-z^{-1})^m$
In your situation you have $\displaystyle n= m +2$. Does this help?
Actually, here is a much easier way to perform the integration. Your integrand is of the form
$\displaystyle \sin((m+1)x)\sin^{m-1}x $
where $\displaystyle m$ is a positive integer. You have that
$\displaystyle = (\sin^{m-1}x)\sin(mx+x) = (\sin^{m-1}x)(\cos(mx)\sin x - \cos x\sin(mx))$
Expanding this, we get
$\displaystyle \cos(mx)\sin^m x - \sin(mx)\sin^{m-1}x \cos x$
Now, can you recognize this as the derivative of something?